Improving the resilience of sorake beach destination: an integrated education and training program to balance the impact of foreign tourist visits - Waruwu, Agustinus; Pranoto, Pranoto (International Journal on Social Science, Economics and Art, 2024)
Sorake Beach is one of the tourist destinations with the main attraction is marine tourism which if managed with good management can attract many foreign tourists, especially tourists who like to do marine activities. The arrival of foreign tourists brings positive and negative impacts. In this research, the impact of tourism on the economic, socio-cultural and environmental conditions is explored so that the real conditions can be known and then compiled into a sustainable tourism destination development plan. The research was conducted using a qualitative method using data collection techniques in the form of observation, interviews, documentation and library literacy to explore the true conditions in the research. The result of the research is the documentation of data on the impact of tourism on economic, socio-cultural and environmental conditions in Sorake Beach. Furthermore, the data is used as the basis for the preparation of community education and training planning to increase the resilience of Sorake Beach tourist destinations.